Ramp Sequence May Explain Synonymous Variant Association with Alzheimer’s Disease in the Paired Immunoglobulin-like Type 2 Receptor Alpha (PILRA) - Justin B. Miller; J. Anthony Brandon; Lauren M. Harmon; Hady W. Sabra; Chloe C. Lucido; Josue D. Gonzalez Murcia; Kayla A. Nations; Samuel H. Payne; Mark T. W. Ebbert; John S. K. Kauwe; Perry G. Ridge (Biomedicines)
Background: The synonymous variant NC_000007.14:g.100373690T>C (rs2405442:T>C) in the Paired Immunoglobulin-like Type 2 Receptor Alpha (PILRA) gene was previously associated with decreased risk for Alzheimer’s disease (AD) in genome-wide association studies, but its biological impact is largely unknown. Objective: We hypothesized that rs2405442:T>C decreases mRNA and protein levels by destroying a ramp of slowly translated codons at the 5′ end of PILRA. Methods: We assessed rs2405442:T>C predicted effects on PILRA through quantitative polymerase chain reactions (qPCRs) and enzyme-linked immunosorbent assays (ELISAs) using Chinese hamster ovary (CHO) cells. RESULTS: Both mRNA (p = 1.9184 × 10−13) and protein (p = 0.01296) levels significantly decreased in the mutant versus the wildtype in the direction that we predicted based on the destruction of a ramp sequence. Conclusions: We show that rs2405442:T>C alone directly impacts PILRA mRNA and protein expression, and ramp sequences may play a role in regulating AD-associated genes without modifying the protein product.